PENGARUH BAHASA ARAB TERHADAP PSIKOLOGI KECERDASAN - Kamus; Nikma Ramadhani; Rahmat Kurniawan (Program Studi Bahasa dan Sastra Arab STAIN Majene, 2022)
This study aims to reveal the importance of learning and plunging into the values of the Qur'an in this case is the Arabic language. The Qur'an came down to this face in order to decide all cases that were deviant due to human activities at that time which were far from the values of failure since the beginning of the dissolution of the prophetic period of Prophet Ibrahim which was fairly long at that time, as a result the descent of Kalamullah created a significant influence. and we can feel the benefits until now. As a way of life, the Qur'an is the greatest miracle of the Prophet Muhammad. Reading it is worship, learning and teaching it makes us the best human beings. The results showed that researchers by mental health experts stated that studying the Qur'an and the values contained in it can increase intelligence. For this reason, Arabic also plays an important role in the process of encouraging as an effort to maximize the value of worship in the Qur'an itself. As mentioned in the editorial of the Qur'an that